Uzroci i laboratorijska dijagnostika pleuralnih izljeva u pasa - Benko, Valerija; Šmit, Iva; Foršek, Jadranka; Radonjić, Aleksandra; Đurić, Vlasta; Jović, Ines; Torti, Marin (2020)
Pleuralne izljeve definiramo kao patološko nakupljanje tekućine u pleuralnoj šupljini, a koji u pasa nastaju posljedično različitim upalnim, sistemskim, metaboličkim, kardiovaskularnim, infekcijskim i neoplastičnim bolestima te traumama, a dijelimo ih na transudate, modificirane transudate i eksudate. Uzroci pleuralnog izljeva su, patofiziološki gledano, porast hidrostatskog tlaka (pr. posljedično zastojnom zatajivanju srca), pad onkotskog tlaka (pr. posljedično hipoproteinemiji), povećana propustnost stijenke krvnih žila (najčešće posljedično upalnoj reakciji) i opstrukcija limfnih žila (najčešće posljedično tumorskom rastu). Najčešći klinički znak u pasa s patološkim pleuralnim izljevima je otežano disanje (respiratorni distres, dispneja). Ostali klinički znaci uključuju: skvrčen, ležeći položaj s ispruženim glavom i vratom, disanje otvorenim ustima, ubrzano i naglašeno abdominalno disanje, a u uznapredovalih slučajeva prisutna je i cijanoza. Postupkom torakocenteze, osim što uklanjamo pleuralni izljev, možemo ga i prouzročiti, a daljnja laboratorijska dijagnostička obrada je ključna za postavljanje sumnje (ponekad i konačne dijagnoze) na uzrok ili uzroke koji su doveli do patološkog nakupljanja tekućine u pleuralnoj šupljini. Svrha je ovog preglednog rada prikazati uzroke i specifične vrste izljeva u pleuralnu šupljinu u pasa, kao i dijagnostički pristup istima.
Pleural effusions are defined as pathologic accumulation of free fluid in the pleural cavity, and in dogs they arise from a variety of inflammatory, systemic, infectious and neoplastic conditions, metabolic disorders, trauma and cardiovascular diseases. Pleural effusions are typically classified as transudates, modified transudates, and exudates. From a pathophysiologic standpoint the accumulation of free fluid can be caused by (1) an increase in hydrostatic pressure (as is the case with congestive heart failure), (2) a decrease in oncotic pressure (i.e. due to hypoproteinemia), (3) increased permeability of the vessel wall (most often as a result of inflammatory reaction) and lymphatic obstruction (most often due to tumor growth). Dogs with pathologic pleural effusions often show heavy breathing (respiratory distress, dyspnea) as the most common clinical sign. Other clinical signs include a crouched, sternal recumbent position with extension of the head and neck, open - mouth breathing, tachypnea, forceful abdominal respiration and cyanosis. Thoracocentesis is used to drain the free fluid, but also to sample pleural effusion, as further laboratory examination is crucial to establish a suspicion and sometimes a definitive diagnosis of the cause or causes that led to the pathological accumulation of fluid in the pleural cavity. The purpose of this review is to present the causes and specific types of effusions in the pleural cavity in dogs, as well as their diagnostic approach.
Bibliografija: 71 jed.
Sažetak ; Summary.
Keywords: Pleuralni izljevi -- Psi -- Laboratorijska dijagnostika